Correlation between 25(OH)D and HbA1c with Diabetic Nephropathy - Meita Hendrianingtyas; Dewi Paramita Yuniarahmi (Postgraduate, University of Mataram, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action. DM patients may develop diabetic nephropathy (ND), marked by decreased glomerular filtration rate (eGFR), also influenced by hypertension. Vitamin D in its active form, 25-hydroxyvitamin D (25(OH)D), regulates insulin secretion and supports pancreatic beta cell survival. The relationship between 25(OH)D, HbA1c, and ND needs evaluation to predict ND earlier. To analyze the correlation between 25(OH)D and HbA1c levels with ND measured by eGFR in DM patients at Diponegoro National Hospital, Semarang. A cross-sectional study of 82 DM patients. 25(OH)D levels were measured by Fluorescent Immunoassay (FIA) and HbA1c by High-Performance Liquid Chromatography (HPLC). eGFR was calculated from creatinine using the CKD-EPI formula. Data analysis used Pearson and regression tests (p<0.25). A weak positive correlation was found between HbA1c and eGFR (p=0.002, r=0.307) and a very weak negative correlation between 25(OH)D and eGFR (p=0.147, r=-0.117). The combined influence of HbA1c, 25(OH)D, and blood pressure yielded R²=0.21. Higher HbA1c increases eGFR, while lower 25(OH)D also associates with higher eGFR. eGFR is influenced by HbA1c, 25(OH)D, and blood pressure by 21%, with other factors explaining the remainder.